2007
DOI: 10.1109/lawp.2007.909969
|View full text |Cite
|
Sign up to set email alerts
|

Very Low Profile and Dielectric Loaded Feeder Antenna

Abstract: In this letter, very low profile planar horn antenna feeders are designed and measured. Using previous results of antennas consisting of a narrow slot on a metallic plane and flanked by two grooves, a further step is given here by reducing the thickness of the prototype. A key factor in the approach is the operation in the transversal slot resonance instead of the usual longitudinal slot resonance. Moreover, by inserting a dielectric material of relative permittivity r 1, the thickness can be further reduced, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 6 publications
1
31
0
Order By: Relevance
“…It was also observed that including a small offset at the end of the disc, o 2 optimized termination for the travelling wave. As discussed in [6], [7], [14], broadside radiation takes place when the period of the corrugated structure is close to the wavelength, d  . With this condition, together with a proper grooves' dimensions tuning, the periodic structure radiates a narrow beam from the excitation of the n = -1 space harmonic (or Floquet mode).…”
Section: Prototype Design and Simulationsmentioning
confidence: 94%
See 1 more Smart Citation
“…It was also observed that including a small offset at the end of the disc, o 2 optimized termination for the travelling wave. As discussed in [6], [7], [14], broadside radiation takes place when the period of the corrugated structure is close to the wavelength, d  . With this condition, together with a proper grooves' dimensions tuning, the periodic structure radiates a narrow beam from the excitation of the n = -1 space harmonic (or Floquet mode).…”
Section: Prototype Design and Simulationsmentioning
confidence: 94%
“…central slot surrounded by annular corrugation), which was first presented in [15] and, soon after, in [6], by introducing a sinusoidal corrugation profile instead of the typical square corrugations or the recently investigated triangular corrugations [16]. A similar idea was also studied in [17], but there the surface was modulated by a sinusoidal spiral function, achieving a circularly polarized leaky wave antenna.…”
mentioning
confidence: 99%
“…These antennas consist of a radiating slot surrounded by straight parallel [23]- [25] or annular concentric [26] corrugations. In the latter case, the structure is usually called Bull's-Eye (BE) antenna.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that this phenomenon can be applied to the design of microwave antenna for improved performance [6][7][8][9]. In [6], a bull's eye corrugated structure is used as the ground plane of a patch antenna.…”
Section: Introductionmentioning
confidence: 99%
“…Since the upper operating frequency of this antenna is determined by the metallic plate thickness, the profile of the antenna is 12 mm. Subsequently, a dielectric material with relative permittivity ε r > 1 is inserted into the grooves [8], and then the profile of this antenna can be further reduced.…”
Section: Introductionmentioning
confidence: 99%